Signals from housing and lending booms - Irina Bunda; Michele Ca' Zorzi (European Central Bank (ECB), 2009)
The contribution of this paper is to revisit the Early Warning System (EWS) literature by analysing selected episodes of financial market crisis, i.e. those preceded by a spell of credit and real estate expansions. The aim is to disentangle instances when this constitutes a natural phenomenon associated with a process of financial development and innovation from those where it constitutes a worrisome signal. We identify economic variables that have leading indicator properties, thus helping to distinguish between “benign” episodes from those likely ending with downward pressures on the exchange rate or even a fully-fledged banking crisis. We find that a large current account deficit, a fall in price competitiveness, strong real growth and high public debt-to-GDP ratio increase the probability that a lending or housing boom would be accompanied by financial market tensions shortly after the peak.
Keywords: E32; F31; F37; 330; credit booms; Early Warning System; Financial crises; House prices; Frühwarnsystem; Finanzkrise; Immobilienmarkt; Kreditmarkt; Spekulationsblase; Welt